Multiprocessing Extensions in SPUR Lisp - Zorn, Ben; Larus, Jim (IEEE Computer, 2002)
The authors describe their multiprocessing extensions to Common Lisp. They have added a few simple, expressive features on which one can build high-level constructs. These consist of a multithreading mechanism, primitives for communication and synchronization (mailboxes and signals), and a feature called futures. A few examples clarify how the primitives work and demonstrate their expressiveness. When Spur Lisp is ported to and optimized on the Spur workstation (a shared memory multiprocessor), programmers can use it to make symbolic programs parallel.